Analisis Pemanfaatan Media Sosial Sebagai Media Pembelajaran Bahasa Mandarin Dan Budaya Tiongkok - Sutandi, Septerianie; Selvia, Selvia (Jayapangus Press, 2024)
With very rapid technological advances, the use of social media has become a lifestyle for the general public in various fields, including education. Social media is a new alternative learning media that can provide changes to the learning system. The Instagram of PT. Bolong Media Indonesia presents content about China in the fields of politics, business, technology, language and culture, etc. The aim of this research is to analyze the use of Instagram PT. Bolong Media Indonesia as a medium for learning Mandarin and Chinese culture. This research is a qualitative descriptive research. This research data was obtained through the process of identifying content of Instagram PT Bolong Media Indonesia and distributing questionnaires. The preparation of the questionnaire and analysis of survey results was carried out based on the Uses & Gratifications Theory. The results of this research are the Instagram of PT. Bolong Media Indonesia is suitable for use as a medium for learning Mandarin language and Chinese culture in Indonesia based on digital literacy, making it easier for students to independently search for sources of information and deepen their understanding and language skills.